Determinants of revenue efficiency in the Malaysian Islamic banking sector - Sufian, Fadzlan; Kamarudin, Fakarudin; Mohd Noor, Nor Halida Haziaton (King Abdulaziz University, 2012)
This paper provides new empirical evidence on the revenue efficiency in the Malaysian Islamic banking sector during the period 2006 to 2010. We also examine the internal and external factors influencing the revenue efficiency of the Islamic banks. The sample comprised of 17 domestic and foreign Islamic banks. We employ the Data Envelopment Analysis (DEA) method to compute the revenue efficiency levels. The results indicate that the domestic Islamic banks have exhibited lower revenue efficiency levels compared to their foreign bank peers. We find that capitalization, market power, and liquidity have positive and significant relationships with Malaysian Islamic banks’ revenue efficiency. The results indicate that the impacts are not uniform across Islamic banks of different ownership forms.